Web Network Statistics Generator and Analyzer - Sivaranjani, B; Priyadharshini, M (International Journal of Computer Sciences and Engineering, 2025)
This project “Web Network Statistics generator and analyzer” has been developed to provide the better security mechanism for intranet services and reporting. There are a range of functions and reports that provide extensive information on complete process of official mail management and file blocker for different set of users those who are logged into this system. It also handles website status and produce a modification guides. This web tracking system is developing by using the PHP as front end with SQLSERVER as back end. The project consists of various modules such as admin, user, registration, web upload, web user monitoring, file transfer watcher, Email blocker. It verifies the hidden images and verifies links & URL’s Connections. It includes the secured gateway system for the entire server system and transactions performing on the process based actions with perspective to the web product development. This system has a range of functions and reports that provide extensive information on all website status and produce a modification guides. This system is platform independent and can be used by any kind of learner. It is designed with robust and easy to implement in any network places. It is highly scalable and provides the feasible updates to make this project efficient and handle by any kind of user